The Montado/Dehesa cow-calf production systems in Portugal and Spain: an economic and resources’ use approach - Costa Freitas, M. B. (2020)
The Montado in Portugal and Dehesa in Spain is a unique agro-silvo-pastoral system designed to overcome food needs in a scarce resource’s environment. The system competitiveness is not clear and it is now under severe threats, caused by extensification or abandonment of less fertile areas and by intensification in more fertile ones. The aim of the undertaken research is to compare the cow-calf production within these systems in Portugal and Spain, identifying their strengths and weaknesses and the main drivers of their evolution, and to compare these systems with other European countries’ systems, ranking their competitiveness and e ciency among other systems in the EU. The research indicates that Montado/Dehesa farms systems are dependent on the type of farming system, its context and management, i.e., on the decision and its context; so, in a context of Mediterranean land system changes, the future of the Montado/Dehesa ecosystem depends on the ability of the cow-calf production systems to face the future and to perceive the modifications needed to overcome new challenges and take advantage of new opportunities.